Estimation of an Unknown Parameter in the Cauchy Problem for a First-Order Partial Differential Equation under Small Gaussian Perturbations - Bondarev, B. V.; Dzundza, A. I.; Simogin, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
On the basis of observation of a realization of a solution of the Cauchy problem, we establish a maximum-likelihood estimate for an unknown parameter. We construct an exponential inequality for the probabilities of large deviations of the estimate from the real value of the parameter.